Hepatocellular carcinoma: resection with adjuvant hepatic artery infusion therapy vs resection alone. A systematic review and meta‐analysis. Issue 4 (21st December 2018) - Moran, Alexandra; Ramos, Lorena Flor; Picado, Omar; Pendola, Fiorella; Sleeman, Danny; Dudeja, Vikas; Merchant, Nipun; Yakoub, Danny
Abstract : Hepatocellular carcinoma (HCC) has a recurrence rate of up to 70% in 5 years after resection, detrimentally lowering survival. The role of adjuvant therapy remains controversial; therefore, the aim of this study was to evaluate the disease‐free and overall survival of patients with HCC, not candidates for transplantation, undergoing resection and adjuvant hepatic artery infusion therapy vs resection alone. Our meta‐analysis showed that adjuvant HAIC improves overall and disease‐free survival after resection, especially in tumors ≥7 cm.